Conformable Hybrid Systems for Implantable Bioelectronic Interfaces - Fallegger, Florian (Advanced materials (Deerfield Beach, Fla.), 2020)
© 2019 The Authors. Published by WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.